Türkiye’s Immigration Landscape: Cultural Exchange and Labor Dynamics with Africa - ÖZUYGUN, Mert Efe (Journal of Central and Eastern European African Studies, 2024)
Türkiye’s relations with the African continent trace back to the periods of the Ottoman Empire’s existence there. Beginning with trade, continuing education, and improving labor force requirements continue to strengthen relations with the Modern Türkiye. As a result of the transformations the African continent has undergone in recent years, Türkiye wants to take advantage of the opportunities in the region, increasing its reputation through civil society organizations and aid agencies, while exerting a protective and reassuring influence in the region through military cooperation. Due to factors triggering migration from African countries, Türkiye and Europe are seen as a new hope for immigrants. In addition to the increasing need for the labor force, affordable education, and scholarship opportunities, the university entrance exam prepared specifically for foreign students also makes Türkiye an attractive center. In this article, you will witness the journey stories of hope that often begin with aspirations to become football players, the changes in the perception of Africans over the years through the power of social media, and the factors influencing this, as well as the importance of arts, music, films, and television series in shaping society. From the challenges faced by African communities seeking hope in a new country to the conveniences provided by government institutions during the integration process, all these processes are addressed in this article.